Coculture of meniscus cells and mesenchymal stem cells in simulated microgravity. (December 2017) - Weiss, William; Mulet-Sierra, Aillette; Kunze, Melanie; Jomha, Nadr; Adesida, Adetola
Abstract Simulated microgravity has been shown to enhance cartilaginous matrix formation by chondrocytes and chondrogenesis of mesenchymal stem cells (MSCs). Similarly, coculture of primary chondrocytes with MSCs has been shown as a strategy to simultaneously retain the differentiated phenotype of chondrocytes and enhance cartilaginous matrix formation. In this study, we investigated the effect of simulated microgravity on cocultures of primary human meniscus cells and adipose-derived MSCs. We used biochemical, qPCR, and immunofluorescence assays to conduct our investigation. Simulated microgravity significantly enhanced cartilaginous matrix formation in cocultures of primary meniscus cells and adipose-derived MSCs. The enhancement was accompanied by increased hypertrophic differentiation markers, COL10A1 andMMP-13, and suppression of hypertrophic differentiation inhibitor, gremlin 1 (GREM1 ). Cartilage: Simulated microgravity promotes cartilage matrix deposition Co-culture of meniscal cartilage-forming cells with fat-derived stem cells can lead to enhanced cartilage matrix production when cultured under simulated microgravity. Adetola Adesida from the University of Alberta in Edmonton, Canada, and colleagues cultured two types of cells found together in the knee—cartilage-forming chondrocyte cells (taken from the meniscus) and mesenchymal stem cells (isolated from the infrapatellar fat pad)—in a rotary cell culture system designed to model weightlessness on Earth. Simulated microgravity enhanced the synergistic interaction between the two types of cells in culture, resulting in more matrix production, but it also prompted the cartilage-forming cells to differentiate towards bone-forming cells, as evidenced by gene expression analysis. These findings suggest that microgravity and simulated microgravity-based culture technologies could help bioengineers grow knee replacements for people with meniscus tears, but increased bone-directed differentiation could pose a possible problem for astronauts on prolonged missions.